Housing for a Lonely Generation - Marija Maric (Footprint)
Organised around the advertising language for three co-living platforms—WeLive, Quarters (now Habyt), and the Collective—this essay frames the corporate housing model as inseparable from the digital media infrastructures that distribute its contents. Building, on one side, upon the existing research in the domain of housing, real estate, and media, and on the other, on the performative reading of the real estate advertisements of the contemporary co-living projects, it positions this housing typology as a genuine product of the 'real-estate-media complex,' referring to the close entanglements of speculative property markets, media infrastructures, and digital technologies in commodification of housing.